The Effect of Changes in Rainfall on Corn Crop Productivity in Kuimasi Village, Fatuleu District, Kupang Regency - Yoritna Djuma; Mikael Samin; Sunimbar Sunimbar (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study aims to determine the effect of changes in rainfall on corn productivity in Kuimasi Village, Kupang Regency. This study uses quantitative methods. The analysis used in this study is simple regression analysis and Pearson Product Moment Correlation Analysis. The data sources used are primary data and secondary data, then the data is collected through documentation and questionnaires. The results of this study show that the variable (X) changes in rainfall have a positive effect on the variable (Y) of corn productivity, which can be seen through the results of a simple linear regression with a Correlation or Relationship (R) value of 0.743. From this output, a coefficient of determination (R square) of 0.552 is obtained, from the variations that occur in corn productivity in Kuimasi Village, Fatuleu District, Kupang Regency. In other words, changes in rainfall contribute 55.2% to changes in corn productivity. While the remaining 44.8% is influenced by other factors outside this research model, such as seed quality, fertilization, soil processing, pest and disease control, and other agroclimatic factors. In this study, rainfall has changed over the past five years, affecting and causing unstable corn productivity.